The Role of the Penghulu in Reproductive and Sexual Health Education for Prospective Brides and Grooms in Tanete Riattang Timur District from an Islamic Family Law Perspective - Afifah. HS, Nur; Hamzah; T, Jamaluddin; Febriany, A. Very (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2025)
This study was motivated by the suboptimal delivery of reproductive and sexual health material in premarital counseling at the Tanete Riattang Timur District KUA, even though the lack of understanding among prospective brides and grooms often contributes to domestic conflicts and divorce. The main questions of this study are what role the penghulu (religious official) plays in reproductive and sexual health education for prospective brides and grooms and how this role is analyzed from the perspective of Islamic Family Law. This study uses a qualitative method with a field research design through a normative juridical, empirical juridical, normative theological, and legal sociological approach. Data were collected through observation, interviews, and documentation, then analyzed descriptively and qualitatively through data reduction, data presentation, and conclusion drawing. The results show that the penghulu has carried out an educational function through marriage guidance, counseling, and facilitation of cross-sector cooperation, but the delivery of reproductive and sexual health material is still limited due to constraints in competence, time, and technical support. Analysis using the maqāṣid al-syarī‘ah theory confirms that the role of the penghulu is in line with efforts to protect life, offspring, and religion, so that this education has a strategic role in ensuring the physical and mental readiness of prospective brides and grooms and preventing domestic disharmony.